Analisis Ketercapaian Standar Kompetensi Lulusan di MTS As Salam - Septiawati, Laras; Eftanastarini, Indah (CV. Creative Tugu Pena, 2020)
This study aims to analyze the challenges of achieving indicators of attitude competency assessment stages on graduate standards. This is important to discuss to ensure the achievement of an institution in eight National Education Standards. This research method uses participatory descriptive research. This research was conducted at As-Salam Mts Bandung. The instrument used refers to seven indicators of graduate standards in the form of interview guidelines. The conclusions of this study are (1) the profile of the achievement of the Graduate Standard indicator shows varying results with an average achievement of 91%. (2) indicators that have not reached the maximum score are the absence of literacy training and seminars for students at school. The recommendations of the results of this study need an in-depth study of the use of the results of assessment of graduate indicators using more authentic instruments. Keywords: Graduate Standards. Literacy, Seminars